If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16(z + 3) = 4(z + -9) Reorder the terms: 16(3 + z) = 4(z + -9) (3 * 16 + z * 16) = 4(z + -9) (48 + 16z) = 4(z + -9) Reorder the terms: 48 + 16z = 4(-9 + z) 48 + 16z = (-9 * 4 + z * 4) 48 + 16z = (-36 + 4z) Solving 48 + 16z = -36 + 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. 48 + 16z + -4z = -36 + 4z + -4z Combine like terms: 16z + -4z = 12z 48 + 12z = -36 + 4z + -4z Combine like terms: 4z + -4z = 0 48 + 12z = -36 + 0 48 + 12z = -36 Add '-48' to each side of the equation. 48 + -48 + 12z = -36 + -48 Combine like terms: 48 + -48 = 0 0 + 12z = -36 + -48 12z = -36 + -48 Combine like terms: -36 + -48 = -84 12z = -84 Divide each side by '12'. z = -7 Simplifying z = -7
| (2x-4)(x+3)= | | 2a-4b=58 | | -a+5=5a+5 | | 3x-7=-3 | | F(5)=20x+11 | | 4x^3+8x^2+3x+6=0 | | q-rb=15a | | 2x+12i=3y+2yi | | 12p=p+24+p | | 18x^2+45x+15=-10 | | 2w+9=-3 | | 2m+5=m+4 | | sin(10x)*cos(5x)=0 | | 3(x^2-10)-3x=6(x^2-2x) | | 4(y+4)+3=39 | | (8y+13)(5y+24)=0 | | (4x+4)(8x+10)=0 | | 9=3-a | | 6h+5+h=-3 | | 2x^3-12x-32x-192=0 | | x-3=-3x-23 | | 10t-4= | | -4x+3=6x+23 | | 3x-4x=-4x-11 | | 8+4m=-12 | | 8g=10+6g | | 9y=1800 | | y=-0.000235x(x-160) | | 2x+1=-2x+17 | | 10x+.10=0x+.35 | | c=hx-e | | 6u=-24 |